PERAN BANK INDONESIA DALAM KEJAHATAN PERBANKAN YANG DILAKUKAN OLEH BANK BALI - Hamja, Hamja (Universitas Wiralodra, 2018)
The existence of a central bank is also needed to regulate and supervise banks so that their activities can develop healthy and run smoothly so that it can encourage economic activities. This is considering that the existence of an impartial regulator will bring banks to carry out their operations efficiently and be able to advance economic development. In the interbank payment system, Bank Indonesia has the duty to regulate and maintain a smooth payment system. Including the problems that occurred in the case of Bank Bali, the task of Bank Indonesia as an institution that regulates and maintains a smooth payment system between BDNI and Bank Bali.